السلفية والسياسة: حالة ماليزية = Political Salafism in Malaysia - Malik, Maszlee (IIUM Press, International Islamic University Malaysia, 2018)
“Political salafism” is among the unexpected phenomenon emerge as a result of Arab Spring. It is observable through active involvement of salafi groups in politics in certain countries affected by revolutions. However, salafī–political advocators seems emerged earlier in Malaysia, compare to their counterparts in Egypt. Malaysian Salafi joined themselves in UMNO party (the United Malays National Organization) in 2009, and justified their involvement in the party as following salafi method, based on the notion of “absolute obedience to the ruler,” ‘prohibition of secession from the ruler,” and “necessity renders prohibited things permissible” Such involvement in political life is considered as bringing mileage to the salafī as well as the political party itself, even though the involvement initially based on gaining certain political benefit. Using historical and descriptive methodology, this article attempts to characterize raison detré as well as religious motives underneath the framework of those salafī advocators.